A Scoring System for the Early Detection of Oral Submucous Fibrosis Based on a Self-administered Questionnaire - Chung-Jung Chiu, DDS, PhD; Wen-Chung Lee, MD, PhD; Chun-Pin Chiang, DDS, PhD (Blackwell Synergy, 2002)
The aims of the present study were to evaluate the frequent clinical complaints of oral submucous fibrosis (OSF) and to develop a scoring system for early detection of the disease by a self-administered questionnaire